Night shift work, chronotype and prostate cancer risk in the MCC‐Spain case‐control study - Papantoniou, Kyriaki; Castaño‐Vinyals, Gemma; Espinosa, Ana; Aragonés, Nuria; Pérez‐Gómez, Beatriz; Burgos, Javier; Gómez‐Acebo, Inés; Llorca, Javier; Peiró, Rosana; Jimenez‐Moleón, Jose Juan; Arredondo, Francisco; Tardón, Adonina; et al. (International journal of cancer, 2015)
Night shift work has been classified as a probable human carcinogen based on experimental studies and limited human evidence on breast cancer. Evidence on other common cancers, such as prostate cancer, is scarce. Chronotype is an individual characteristic that may relate to night work adaptation. We evaluated night shift work with relation to prostate cancer, taking into account chronotype and disease severity in a population based case‐control study in Spain. We included 1,095 prostate cancer cases and 1,388 randomly selected population controls. We collected detailed information on shift schedules (permanent vs. rotating, time schedules, duration, frequency), using lifetime occupational history. Sociodemographic and lifestyle factors were assessed by face‐to‐face interviews and chronotype through a validated questionnaire. We used unconditional logistic regression analysis adjusting for potential confounders. Subjects who had worked at least for one year in night shift work had a slightly higher prostate cancer risk [Odds Ratio (OR) 1.14; 95%CI 0.94, 1.37] compared with never night workers; this risk increased with longer duration of exposure (≥28 years: OR 1.37; 95%CI 1.05, 1.81; p‐trend = 0.047). Risks were more pronounced for high risk tumors [D'Amico classification, Relative Risk Ratio (RRR) 1.40; 95%CI 1.05, 1.86], particularly among subjects with longer duration of exposure (≥28 years: RRR 1.63; 95%CI 1.08, 2.45; p‐trend = 0.027). Overall risk was higher among subjects with an evening chronotype, but also increased in morning chronotypes after long‐term night work. In this large population based study, we found an association between night shift work and prostate cancer particularly for tumors with worse prognosis. What's new? Up to 20% of workers do night‐shift work, which may increase the risk of some cancers. In this study, the authors found that long‐term night‐shift work was associated with an increased risk of prostate cancer and decreased survival. Overall risk was higher among workers with an evening chronotype (i.e., a preference for working in the evening vs. in the morning), but risk also increased for morning chronotypes if the duration of night‐shift work increased. These results may improve our understanding of prostate cancer etiology and potential prevention strategies.